2017
DOI: 10.3390/ijms18081616
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA Inhibits Epithelial-Mesenchymal Transition in Bladder Cancer Cells via Modulation of STAT3-CCL2 Signaling

Abstract: Tanshinone IIA (Tan-IIA) is an extract from the widely used traditional Chinese medicine (TCM) Danshen (Salvia miltiorrhiza), and has been found to attenuate the proliferation of bladder cancer (BCa) cells (The IC50 were: 5637, 2.6 μg/mL; BFTC, 2 μg/mL; T24, 2.7 μg/mL, respectively.). However, the mechanism of the effect of Tan-IIA on migration inhibition of BCa cells remains unclear. This study investigates the anti-metastatic effect of Tan-IIA in human BCa cells and clarifies its molecular mechanism. Three h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 51 publications
2
42
0
Order By: Relevance
“…However, there is no evidence at the cellular level or from animal models demonstrating such an effect of the combination of Tan IIA with DDP on NSCLC progression. The study presented herein indicates that the combination of Tan IIA with DDP diminishes It has been reported that Tan IIA inhibits the migration and invasion ability of bladder cancer cells (Huang, Chang, Liao, & Chiu, 2017) and Tan IIA combined with adriamycin inhibits migration and invasion ability in NSCLC (Xie et al, 2016). Our findings also showed that Tan IIA combined with DDP could inhibit the migration and invasion ability of A549 and PC9 cells in a synergistic manner.…”
Section: Potential Target Proteins Of Tan Iia and The Kegg Pathway supporting
confidence: 70%
See 1 more Smart Citation
“…However, there is no evidence at the cellular level or from animal models demonstrating such an effect of the combination of Tan IIA with DDP on NSCLC progression. The study presented herein indicates that the combination of Tan IIA with DDP diminishes It has been reported that Tan IIA inhibits the migration and invasion ability of bladder cancer cells (Huang, Chang, Liao, & Chiu, 2017) and Tan IIA combined with adriamycin inhibits migration and invasion ability in NSCLC (Xie et al, 2016). Our findings also showed that Tan IIA combined with DDP could inhibit the migration and invasion ability of A549 and PC9 cells in a synergistic manner.…”
Section: Potential Target Proteins Of Tan Iia and The Kegg Pathway supporting
confidence: 70%
“…It has been reported that Tan IIA inhibits the migration and invasion ability of bladder cancer cells (Huang, Chang, Liao, & Chiu, ) and Tan IIA combined with adriamycin inhibits migration and invasion ability in NSCLC (Xie et al, ). Our findings also showed that Tan IIA combined with DDP could inhibit the migration and invasion ability of A549 and PC9 cells in a synergistic manner.…”
Section: Discussionmentioning
confidence: 99%
“…Tanshinone IIA is a major bioactive component from the famous medical herb Salvia miltiorrhiza that was reported to attenuate the proliferation of bladder cancer cells (Table ). Further study revealed that tanshinone IIA suppressed EMT in bladder cancer cells via the modulation of the STAT3‐CCL2 signaling pathway . In addition, tanshinone IIA blocked EMT by regulating the TGF‐β/Smad pathway in peritoneal fibrosis .…”
Section: Small Molecules Against Emtmentioning
confidence: 99%
“…Further study revealed that tanshinone IIA suppressed EMT in bladder cancer cells via the modulation of the STAT3-CCL2 signaling pathway. 32 In addition, tanshinone IIA blocked EMT by regulating the TGF-β/Smad pathway in peritoneal fibrosis. 116 From these data, it was suggested that compounds that target EMT might have both antifibrotic and anticancer…”
mentioning
confidence: 99%
“…Furthermore, STAT1 was also proved as the direct target of SARI in colon cancer cells, evidenced by Co-IP and IF staining, as indicated in intestinal epithelial cells. 18 Other transcriptional regulation factors of MCP-1, including NF-κB 30,31 and STAT3, 32,33 were up-regulated in colon tissues of SARI −/− mice in CAC, but demonstrated not to be the direct target of SARI in colon cancer cells. The inverse correlation between SARI and p-STAT1 was also observed in colon malignant tissues of patients, whereas SARI mRNA expression was positively correlated with STAT1 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%